A Technological Framework for the Authoring and Presentation of T-learning Courses - Bellotti, Francesco; Vrochidis, Stefanos; Ramel, Sophie; Tsampoulatidis, Ioannis; Lhoas, Pascal; Pellegrino, Matteo; Bo, Giancarlo; Kompatsiaris, Ioannis (International Journal of Emerging Technologies in Learning (iJET), 2008)
Broadcasting interactive learning applications through the digital TV promises to open new pedagogical perspectives, also in a life-long learning perspective, given the wide penetration of the medium. This article proposes an open flexible and composable framework for the development, the delivery and the presentation of t-learning courses in interactive digital TV (iDTV). The framework is divided into two main parts: the production side, where the course is prepared and the client side, where it is presented on iDTV, and where the user can perform the educational interaction. The course production is supported by an ad-hoc designed authoring tool, while the runtime user interaction on iDTV is managed by a multimedia course player providing personalization services and a library of educational and entertainment elements and services. Seven experimental t-learning courses were created by pedagogical experts in several knowledge domains and served as an important test and evaluation bench for the framework, in view of the upcoming extensive end-user testing.